Efeito da utilização de nanotubos de carbono de paredes múltiplas como carreadores na produção de anticorpos específicos anti-anaplasmose em camundongos - Pimentel, Leticia Santos (2018)
Bovine anaplasmosis is caused by the intraerythrocytic gram-negative bacterium Anaplasma marginale. The disease is distributed worldwide in the tropical and subtropical regions of the Americas, Europe, Australia, Africa and Asia and is related to significant economic losses in livestock such as low weight gain, decrease in milk production, abortions, costs of animal treatment and mortality losses. Carbon nanotubes (CNTs) are carbon allotropes composed of graphene sheets organized in tubular form. Due to its incredible mechanical resistance and its ability to cross biological membranes and deliver biomolecules in the cytoplasm, CNTs have proven to be an interesting tool for the development of vaccines. The aim of this work is to characterize the interaction and to evaluate the potential of the synthetic peptide Am1 coupled to Multi-Walled Carbon Nanotubes (MWCNT) to induce the production of antigen-specific antibodies against A. marginale in comparison to the immunization with the peptide administered without the nanoparticles as carriers. Thus, Zeta Potential, absorption spectroscopy in the Fourier Transform infrared spectroscopy (FT-IR) and Electron Transmission Electron Microscopy (TEM) characterized the interaction. BALB/c mice were immunized via three subcutaneous injections at fifteen-day intervals and then challenged with 3x10⁵ erythrocytes infected with A. marginale. The animals were evaluated for weight change, survival and humoral immune response by Enzyme-linked immunosorbent assay (ELISA). The interaction was stable and with less tendency to agglomeration. There was no significant difference in weight loss between the groups and no mortality. Immunization with the Am1 peptide coupled to MWCNT induced antibody production similar to the Am1 peptide with Freund's Adjuvant. In conclusion, animals immunized with the Am1 peptide coupled to MWCNT did not present an immune response superior to that presented by the animals immunized with the peptide alone.